A Window Into Mental Health: Developing and Pilot-Testing a Mental Health Promotion Intervention for Mexican Immigrants Through the Ventanilla de Salud Program - Martínez Rodríguez, Delia Lilian; González Vázquez, Tonatiuh; Márquez Serrano, Margarita; Groot, Mary de; Fernandez, Alicia; Gonzalez Casanova, Ines (Frontiers in Public Health, 2022)
Background Mexican immigrants in the United States face mental health challenges, disparities, and limited access to healthcare; however, mental health promotion efforts specifically targeting this population have been insufficient. The objective of this study was to develop and test a mental health promotion intervention based on protective mental health factors and coping strategies for Mexican immigrants recruited through a free, consulate-based program in Atlanta. Material and Methods Working with the Ventanilla de Salud program, we conducted a longitudinal study in three phases: formative research and design, pre-intervention assessment and post-implementation evaluation. The intervention was designed based on the health promotion model and interviews with stakeholders. Qualitative information was collected by semi-structured interviews with participants before and after the intervention. Quantitative outcomes were knowledge about protective factors and coping mechanisms, and psychosocial distress. Differences were assessed using the Wilcoxon non-parametrical test. Intent-to-treat analysis was conducted with all participants who signed the informed consent (carrying last observation forward), and a complete case analysis was conducted with those who attended at least 70% of the sessions and completed the post- implementation evaluation. Results Twenty-five participants were enrolled in the intervention. Mean age was 38 years, and the majority were women. Only nine participants attended at least 70% of the sessions and completed the final evaluation. Men, those who did not complete high school, and workers in service or construction jobs were more likely to drop out. Knowledge about protective factors [pre- vs. post-intervention median (inter-quartile range) = 111 (100, 120) vs. 115 (100, 124)] and coping mechanisms [96 (85, 104) vs. 99 (90, 110)], as well as psychosocial distress [3 (2, 3) vs. 2 (2, 3)] improved after the intervention in both intent-to treat and complete case analyses (p < 0.05). Qualitative results also support improvements in targeted protective factors. Discussion The intervention was successful in improving psychological distress among Mexican immigrants. These results support the implementation of evidence-based mental health promotion interventions among Mexican immigrants via free and familiar programs. A limitation was the high attrition; future studies should explore approaches to improve retention in this population.